Construction and Testing Index Peace Indonesia - Madjid, Adnan; Malik, Ichsan; Susilawati, Ningsih (The Republic of Indonesia Defense University, 2016)
This research aims to analyze on a measuring instrument for peace in Indonesia, not only measure conflict resolution but also the prevention of conflict. Measuring instrument that will be created is intended to make the Indonesia Peace Index as analytical framework of conflict and peace, especially in Indonesia. Research design using qualitative descriptive study approach. The results of this study indicate that the DKI Jakarta and Papua is a region with the highest intensity conflict. Moreover, the conflict is the dominant social conflict with the highest actors as perpetrators of conflict is the public, this is due to structural factors are still frequently occur and not be solved completely by the government..